2020
DOI: 10.1080/20008198.2020.1776563
|View full text |Cite
|
Sign up to set email alerts
|

A framework of meaning attribution following loss

Abstract: The loss of a loved one causes the world and the place of the bereaved survivor in it to change irreversibly. A key aspect of the grieving process is the integration of the loss in the bereaved survivor's life story, identity change, and a new future orientation through meaning attribution. Meaning attribution can have favourable or unfavourable effects on the grieving process and hence determines the extent to which a loss disrupts the bereaved survivor's functioning. A framework of meaning attribution after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 65 publications
2
18
0
Order By: Relevance
“…While there are some evidence-based practices for PGD (48,49), there has not been efficacy studies on treatment of traumatic loss (50), future efficacy studies are needed which integrate both PTSD and grief treatment interventions to provide trauma-informed services for SMI clients among whom, multi-morbidity is common. The finding that being African American was associated with increased likelihood of having both PTSD and probable PGD is consistent with the social and cultural determinants of traumatic loss/grief (51), in which determinants such as cultural, social factors related to loss may facilitate or complicate the grieving process and therefore call for culturally sensitive care for traumatic grief.…”
Section: Discussionsupporting
confidence: 73%
“…While there are some evidence-based practices for PGD (48,49), there has not been efficacy studies on treatment of traumatic loss (50), future efficacy studies are needed which integrate both PTSD and grief treatment interventions to provide trauma-informed services for SMI clients among whom, multi-morbidity is common. The finding that being African American was associated with increased likelihood of having both PTSD and probable PGD is consistent with the social and cultural determinants of traumatic loss/grief (51), in which determinants such as cultural, social factors related to loss may facilitate or complicate the grieving process and therefore call for culturally sensitive care for traumatic grief.…”
Section: Discussionsupporting
confidence: 73%
“…Research has shown that PGD can be discriminated from PTSD, depression and anxiety disorders e.g., [ 41 , 42 ]. In general, grief is a highly individualized reaction that depends not only on the characteristics of the bereaved person but also on the relationship to the deceased and circumstances of the loss as well as other social and cultural factors [ 43 ].…”
Section: Ecological Grief and Bereavement Researchmentioning
confidence: 99%
“…Specific attention needs to be paid to the management and treatment of bereaved individuals. Grief interventions taking into account the complex circumstances of the loss, such as ritual omissions and other cultural and intergenerational determinants of meaning attribution (Smid, 2020), may support meaning reconstruction following loss and thereby contribute towards increasing connectedness and inspiring hope. The pandemic affects the traditional means of delivery of psychosocial services, including psychological treatments for mental disorders.…”
Section: Setting Policy and Designing Intervention Strategiesmentioning
confidence: 99%